Analisis Tingkat Kebisingan Peralatan Produksi Terhadap Kinerja Karyawan - Kholik, Heri Mujayin; Krishna, Dimas Adji (Jurnal Teknik Industri, 2012)
Machines and tools was used to support the production process have the potential effect to cause noise. Noise is the unwanted sound that interfere and endanger health. This research aimed to analyze the effect of noise level on the performance of the employees. Data collection was done by doing direct observation and questionnaires to workers in some sampling points. Processing data using the t test to determine noise level and simple linear regression to determine the effect of noise level on employee performance. Conclusion from data processing it was known that the noise level in the work area Power Plant II showed significant differences with the Threshold Limit Value (TLV) set by the government namely 98.599dB (A), while TLV set by the government for the work area (Industry) is approximately 85 dB (A). Results of simple linear regression analysis indicate that the value of t test was 10.227, this value was greater than t table namely 2.013. Value of significant level is 0.000 less than a 0.05. These results indicate that the noise in the work area Power Plant II had a significant impact on employee performance.Â